Lamellar ichthyosis and chronic-recurrent tinea corporis. Case report and literature review. - Milano, A. (European Journal of Pediatric Dermatology, 2023)
Autosomal recessive congenital ichthyosis, which is usually linked to mutations in the TGM1 gene, includes a more frequent lamellar form and a more severe erythrodermic form. At birth, the patient has thickened, shiny skin resembling a collodion membrane; this then detaches and turns into ichthyotic hyperkeratosis. Ichthyotic skin predisposes to fungal infections, sometimes extensive and persistent. A patient suffering from lamellar ichthyosis who underwent extensive and persistent for 13 years tinea corporis caused by Trichophyton rubrum was presented and a review of the cases present in the literature was performed.